Understanding Characterisation of Managerial Process : Is It Useful For Managers ? - Chariri, Anies (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1997)
Some research findings indicate that there are different views of what managers really do in managing their organisations. One of them shows that what managers actually do cannot be classified into planning, organising, leading, and controlling. As a result, one might claim that understanding characterisation of managerial process is useless. However, in this paper it is argued that understanding characteristics of mana gerial process is useful for managers to help them cope with the rapid changes in business environment. It is also claimed that managerial process is a political system and a game that take place in a wide arena. It is highly interdependent, contextual, less systematic, and changeable. Managerial process also involves the need for setting agenda, building network, and managing discourses, interactions, symbols, and organisational politics. Finally, it is believed that understanding characterisation of managerial process lead managers to have deep understanding of organisational dynamics and changes in business environment, and to have special skills that are required to cope with the changing environment.